Change in the "goalkeeper wall" adopted for the training of libero in the volleyball - Lunato, C.; Ceruso, R.; Izzo, R. (Journal of Human Sport & Exercise, 2020)
Research revealed that a soccer goalkeeper and a volleyball libero player have multiple characteristics in common. A fundamental motor gesture in both sports is "dig", a movement that requires a certain level of motor skill. The objectives set at the beginning of this experimentation are the improvement of explosive strength and reactivity. The latter specifically given the variability of the trajectories of the ball. 41 athletes divided between goalkeepers and libero players, aged around 15 years who took part in the respective regional sports championships were taken for observation. The "Reach" and "Vertec" tests were used to obtain the elevation data in cm. In addition, innovative tests were introduced which analyse the technical skills based on the role and play ability. Once the incoming data were obtained, the athletes underwent 2 sessions per week for 2 months to train the characteristics in common between the two roles. At the end of the training period, the athletes were again subjected to the tests mentioned above to find potential changes. At the end of the training program, a clear improvement of the whole sample examined emerged.